The Quest for the Blueprint of the Nuclear Pore Complex - Glavy, Joseph S. (Protein J, 2019)
During my postdoc interview in June of 1998, I asked Günter why he was moving more towards the nucleus in his latest studies. He said, “Well Joe, that’s where everything starts.” By the end of the interview, I accepted the postdoc. He had a way of making everything sound so cool. Günter’s progression was natural, since the endoplasmic reticulum and the nucleus are the only organelles that share the same membrane. The nuclear envelope extends into a double membrane system with Nuclear Pore Complexes embedded in the pore membrane openings. Even while writing this review, I remember Günter stressing; it is the Nuclear Pore Complex. Just saying Nuclear Pore doesn’t encompass the full magnitude of its significance. The Nuclear Pore Complex is one of the largest collection of proteins that fit together for an overall function: transport. This review will cover the Blobel lab contributions in the quest for the blueprint of the Nuclear Pore Complex from isolation of the nuclear envelope and nuclear lamin to the ring structures.